A Simple and Efficient One-Pot Route for the Synthesis of 3-[1-Aryl(Alkyl)-2-Pyridin-2-yl-Ethyl]-4-Hydroxy-6-Methyl-2H-Pyran-2-Ones under Catalyst-Free Conditions. (21st April 2022) - Hoseinpour, Mahdieh; Mohebat, Razieh; Nateghi, Mohammad Reza; Kalantari Fotooh, Forough
Abstract: Reaction between 4-hydroxy-6-methyl-2H-pyran-2-one and aldehydes with 2-methylpyridine in dioxane under catalyst-free conditions provided a simple and efficient one-pot route for the synthesis of 3-[1-aryl(alkyl)-2-pyridin-2-yl-ethyl]-4-hydroxy-6-methyl-2H-pyran-2-ones. The reaction is characterized by inexpensive and easily available starting materials, the formation of a single product, high yields of biologically active products, and a simple work-up process. Graphical Abstract: